2010
DOI: 10.1073/pnas.1002291107
|View full text |Cite
|
Sign up to set email alerts
|

Neural inhibition enables selection during language processing

Abstract: Whether grocery shopping or choosing words to express a thought, selecting between options can be challenging, especially for people with anxiety. We investigate the neural mechanisms supporting selection during language processing and its breakdown in anxiety.Our neural network simulations demonstrate a critical role for competitive, inhibitory dynamics supported by GABAergic interneurons. As predicted by our model, we find that anxiety (associated with reduced neural inhibition) impairs selection among optio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
133
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(155 citation statements)
references
References 52 publications
(47 reference statements)
19
133
0
1
Order By: Relevance
“…The results of a recent study using a verb-generating task quite similar to the one we used is also in agreement with our findings (Snyder et al 2010). This study suggested that adults scoring high on an anxiety symptom scale also demonstrated deficient abilities in particular forms of word generation tasks.…”
supporting
confidence: 93%
“…The results of a recent study using a verb-generating task quite similar to the one we used is also in agreement with our findings (Snyder et al 2010). This study suggested that adults scoring high on an anxiety symptom scale also demonstrated deficient abilities in particular forms of word generation tasks.…”
supporting
confidence: 93%
“…Word generation parallels picture naming insofar as the contextual information provided by c (e.g., a word or a picture) can potentially map onto more than one word and calls for goal-directed semantic processing (see esp. Snyder and Munakata, 2008;Snyder et al, 2010Snyder et al, , 2011aKurland et al, 2014). However, typical word generation tasks (e.g., verb generation, Petersen et al, 1988;Raichle et al, 1994) and other variants (cf.…”
Section: Executive Control In Speech I: Word Productionmentioning
confidence: 99%
“…Planum temporal forms the heart of Wernicke's area and besides ϭϳ being involved in the processing of language has also been implicated in auditory spatial processing. A recent fMRI study demonstrated that anxiety being associated with reduced neural inhibition impairs selection between options and associated prefrontal cortical activity during selection and retrieval of words from semantic memory with a verb generation task (Snyder et al, 2010). The authors of the study focussed on the relation between anxiety and the activity specifically in left ventrolateral prefrontal cortex (VLPFC).…”
Section: Discussionmentioning
confidence: 99%